Antidepressants: Relationship to the Time to Psychiatric Readmission and Probability of Being in Hospital in Depressive Patients - Warnke, Ingeborg; Nordt, Carlos; Moock, Jörn; Kawohl, Wolfram; Rössler, Wulf (Frontiers in Public Health, 2014)
Introduction: Although antidepressants play a major role in treating patients with depression, it is unclear which specific antidepressants are more efficacious than others. This study aims to analyze the relationship between several antidepressant substances and the time to readmission as well as the probability of being in hospital in a given week by using prescription data. Methods: The database was health-insurance claim data from the new Federal States in Germany. The analysis consisted of all patients with unipolar depression at their index admission in 2007 (N=1803). Patients were followed up for two years after discharge from index hospitalization. Statistical analyses were conducted by discrete-time hazards models and General Estimation Equation models (GEE), accounting for various predictors. Results: Of all prescribed antidepressant substances, sertraline was related to an increased time to readmission by 37% and to a reduction in the probability of being in hospital in a given week by 40%. However, it was prescribed to only about 5% of the patients. Conclusion: In this study, only sertraline appeared to have clinical and economic advantages. It is remarkable that just a minority of patients received sertaline in our study, thus differing from the prescription pattern in the US.